Resolving GABAA/benzodiazepine receptors: cellular and subcellular localization in the CNS with monoclonal antibodies - Richards, JG (J Neurosci, 1987)
Monoclonal antibodies, raised against a purified GABAA/benzodiazepine receptor complex from bovine cerebral cortex, have been used to visualize the cellular and subcellular distribution of receptorlike immunoreactivity in the rat CNS, cat spinal cord, and bovine and postmortem human brain. Two different antibodies have been used for these studies; bd-17 recognizes the beta-subunit (Mr 55 kDa) in all the species tested, whereas bd-24 recognizes the alpha-subunit (Mr 50 kDa) of bovine and human but not rat and cat tissues. In bovine and human brain, both antibodies produced very similar staining patterns, indicating a homogeneous receptor composition, at least in the brain areas investigated. The general distribution and density of receptor antigenic sites in all tissues studied were very similar to that of benzodiazepine binding sites radiolabeled with 3H-Ro 15–1788 and of glutamate decarboxylase (GAD)-stained nerve terminals. The results demonstrate a very high receptor density (around neuronal cell bodies and processes or less discretely distributed) in the rat olfactory bulbs, cerebral cortex, ventral pallidum, islands of Calleja, globus pallidus, hippocampus, dentate gyrus, substantia nigra, geniculate nuclei, inferior colliculus, cerebellum, reticular formation, spinal cord, and retina. In contrast, no receptors could be detected in white matter, pineal, pituitary, adrenals, and superior cervical ganglia. Only among the cerebellar layers did we observe a conspicuous difference between the staining intensity and the radiolabeling. In bovine and postmortem human brain, e.g., hippocampus, dentate gyrus, cerebral cortex, and substantia nigra, the same close correlation between the immunohistochemical and radiohistochemical findings was observed. At the electron microscopic level, the immune reaction product in the rat substantia nigra and globus pallidus, for example, was localized to pre- and postsynaptic membranes of axodendritic and axosomatic synapses. Whether the presynaptic labeling represents GABA autoreceptors is discussed. In the near future, the monoclonal antibodies will be used in double-labeling experiments with GAD to identify those GABAergic projections that are modulated by benzodiazepine minor tranquillizers. Furthermore, they could also be used, in studies of postmortem human brain, to diagnose receptor dysfunction possibly associated with CNS disorders such as epilepsy.